Palaeoproterozoic (Eburnean) domain of Mayombe belt (Congo-Brazzaville) : origin and tectono-metamorphic evolution - (:unkn) unknown (My University, 2019)
The Mayombe belt is the congolese part of the Araçuaï-West Congo belt system which extend from eastern margin of Brazil to western margin of central Africa. It runs parallel to the Atlantic coastline with NW-SE trend. Considering geochronological data, it is subdivided into two lithostratigraphic domains : (i) the Paleoproterozoic domain and (ii) the Neoproterozoic domain. The Paleoproterozoic domain of the Mayombe range corresponds to the inner part of the belt and is characterized by the coexistence of para and orthoderived rocks deformed and metamorphosed to varying degrees. These rocks are distributed among the three main lithological Groups : (i) the Loémé Group, (ii) the Loukoula Group and (iii) the Bikossi Group. Structural analysis of Loémé and Loukoula Groups shows folded and fractured stuctures. In the Loémé Group, folds trend NE-SW, NNE-SSW and N-S while in the Loukoula Group, the main shortening trends NE-SW. The Bikossi Group is characterized by folds oriented in the directions identified in the preceding Groups. The geochemical study carried out on samples from the Paleoproterozoic domain of the Mayombe belt shows that the latter is heterogeneous, by involving rocks of various origin and lithology. The petrological characterization of Loémé and Loukoula Groups shows that they are affected by at least two distinct metamorphic events that overlap. The first event is characterized by garnet-biotite-oligoclase parageneses in metapelites and by the development of brown hornblende in metabasites, thus allowing the evolution context to be situated in the amphibolite facies. The second event is recorded differently in Loémé Group and Loukoula Group. It consits respectively in garnet-biotite-oligoclase assemblages in the Loemé Group and in chlorite-albite-epidote paragenesis in the Loukoula Group. Samples from Bikossi Group present only traces of a single metamorphic event marked by garnet-biotite-muscovite and garnet-chloritoid-chlor
Keywords: African Research